An open source solution to spell checking and grammar checking add-in for open office writer - Dimalen Editha D.; Dimalen, Davis Muhajereen D. (2007)
Writing manuscripts, communications and other forms of documents that include Tagalog can be very difficult, and daunting task if there are no available tools that can check its spelling and grammar. Hence, a Tagalog spell checker and grammar checker add-in for OPenOffice Writer has been developed. Since Tagalog is a free-word order language, processing of text is very complex. This research addressed several issues in the development of the add-in. These word processing tools are being developed for OpenOffice Writer word processing application. OpenOffice Writer is a non-propriety software ( a free ware) that is readily available for all users. The spell checker and grammar checker checks the spelling of the word, incomplete sentences, awkward phrases, wordiness and poor grammar construction. The research has been tested and evaluated using a separate program that automatically computes the execution of time in checking each document written in Tagalog. The result showed better results in spell check and grammar checking, respectively. It can also successfully spell checked words (inflected or not) as long as root words are found in the lexicon. It can also spell check words with hyphen or apostrophe. In addition, it can check words that are not present in the lexicon due to the stemmer employed in the system. New words can be generated out of the given root words which is exponential. This is due to the stemmer employed in the system which means the lexicon is very powerful in handling a very large wordlist.
Keywords: Open source software; OpenOffice Writer; Word processing